1996
DOI: 10.1177/076737019601100304
|View full text |Cite
|
Sign up to set email alerts
|

Standardisation ou adaptation des échelles de mesure à travers différents contextes nationaux: L'exemple d'une échelle de mesure de l'innovativité

Abstract: Cet article évalue l'adaptabilité inter-pays d'une échelle de mesure de l'innovativité des consommateurs pouvant s'appliquer à divers domaines spécifiques de la consommation (Goldsmith et Hofacker, 1991). Cette échelle a été développée, testée et validée aux Etats-Unis uniquement. L'adaptabilité de l'instrument à d'autres contextes est évaluée dans le domaine spécifique du cinéma, à travers l'étude de ses propriétés psychométriques dans trois pays (Canada, France et Israël). Les implications théoriques, méthod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
2
0
3
Order By: Relevance
“…Parasuraman et al, 1988), one must notice that factor loadings, alpha coefficients, extracted variance, and fit indices decline as one moves away from the United States. Nyeck et al (1996) found a similar pattern of results in a study that evaluates the standardization or adaptation of a consumer innovativeness scale. In that case, their indices for the French sample were lower than those founded for the Quebecer sample.…”
Section: Discussionsupporting
confidence: 66%
“…Parasuraman et al, 1988), one must notice that factor loadings, alpha coefficients, extracted variance, and fit indices decline as one moves away from the United States. Nyeck et al (1996) found a similar pattern of results in a study that evaluates the standardization or adaptation of a consumer innovativeness scale. In that case, their indices for the French sample were lower than those founded for the Quebecer sample.…”
Section: Discussionsupporting
confidence: 66%
“…(Roehrich, 1994). L'innovativité est entendue dans un système social dans lequel l'individu est comparé aux autres pour définir sa vitesse d'adoption de la nouveauté (Nyeck et al, 1996). L'utilisation de nouveaux produits est régie par des normes sociales qui influencent le comportement d'adoption de la nouveauté qui est à l'origine défini comme un trait de personnalité positif (Midgley et Dowling, 1978).…”
Section: Les Outils D'aide à La Vente En Quête De Réalismeunclassified
“…Golf innovativeness: this study used the Domain Specific Innovativeness (DSI) scale adopted from Goldsmith and Hofacker (1991) to measure innovativeness in a golf product context (see goods and services in other studies (e.g. Goldsmith et al, 1995;Nyeck et al, 1996). Golf Innovativeness was measured on a 6-item, 5-point Likert-type scale from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Survey Instrumentmentioning
confidence: 99%